THE MODERATING IMPACT OF CORRUPTION: UNDERSTANDING SMEs GROWTH AND CREDIT ACCESSIBILITY FROM BANKS (Journal of the Management Sciences, 2025)
Universally, SMEs have been acknowledged to be engines of growth and development given their contributions to employment and reduction in abject poverty while on the other hand, corruption generally is seen as one of the causes of poverty. Accordingly, this paper focused on moderating the role of corruption in Deposit Money Banks’ Credit accessibility and SMEs’ growth in Nigeria. Methodologically, an Ex-post facto research design was adopted through sourcing data from annual reports of companies coupled with relevant publications The outcome of the data analysis revealed that corruption has a positive and significant effect on the relationship between Deposit money Bank credit accessibility and SMEs’ growth in Nigeria, since the P-value is greater than 5%. The study recommended that even though corruption has a positive and significant effect as a moderating role in Nigeria, there is a global cry against it as corruption practices cause distortions in the economic system. It also impairs hard work, diligence and efficiency. It can diversify resources meant for society's development to private and personal use and a burden to borrowers. Hence, the recommendation was crafted to eradicate corruption attitudes among loan seekers, bankers and the government.
Keywords: Deposit Money Banks, Corruption, SMEs, Growth, Nigeria